Establishment of a highly efficient and low cost mixed cellulase system for bioconversion of corn stover by Trichoderma reesei and Aspergillus niger. (March 2021) - Shen, Lijun; Su, Yingjie; Sun, Yang; Wang, Gang; Chen, Huan; Yu, Xiaoxiao; Zhang, Sitong; Chen, Guang
Abstract: The high cost of cellulase production is one of the main obstacles for the conversion of lignocellulose into high valued products. As a widely existing biomass resource, corn stover can be used to reduce the cost of cellulase production. In this study, Parameters of producing cellulase by Trichoderma reesei were optimized using Response Surface methodology, the optimum conditions were as follows: 3.84% solid acid pretreated corn stover, 1.19% yeast extract, initial pH of 5.01, 0.12% glycerol monostearate, 0.25% Na2 HPO4, with 3% inoculum content for 12 days at 30 °C. Filter paper activity (FPA) of Trichoderma reesei was increased by 180% to 13.44 IU/mL. Enzymatic hydrolysis experiments were performed on different pretreated corn stovers with Trichoderma reesei cellulase produced under optimal conditions, and the highest cellulose conversion efficiency reached 62.39%. In addition, a blend of Trichoderma reesei cellulase at a concentration of 30 FPU/g cellulose and Aspergillus niger beta-glucosidase at a concentration of 50 FPU/g cellulose could effectively hydrolyse alkali pretreated corn stover, resulting in an improvement in the enzymatic hydrolysis efficiency by 17.26% compared to Trichoderma reesei cellulase alone. In parallel, the mixed enzymes achieved an equivalent enzymatic effect with that of commercial cellulase (Novozymes, Cellic Ctec2) at the same concentration. These data suggested that solid acid pretreated corn stover was a promising carbon source for fungal cellulase production for effective saccharification of corn stover biomass. Glycerol monostearate was first found to have a strong induction effect on enzyme production. The development of a high efficiency and low-cost mixed enzyme system had a potential application in future industrialization scale. Graphical abstract: Image 1 Highlights: Corn stover pretreated with solid acid as the only carbon source for cellulase production by Trichoderma reesei. A non-ionic surfactant, the addition of glycerol monostearate induces the yield of cellulase by Trichoderma reesei.